A chemical sensor for alternative barriers using NIR spectroscopy. Issue 4 (18th February 2016) - Herzberg, Jan C.; Stylianou, Marinos; Pourjabbar, Anahita; Kostarelos, Konstantinos
Abstract : Remediation of contaminated sites often includes the use of alternative barriers as a passive treatment method for a variety of contaminants and sites. Alternative barriers, in turn, require a means for monitoring their performance directly, without the need for costly sampling. It is ideal that the monitoring system provide the data in real time and remotely. When combined with optical fibres, near-infrared (NIR) spectroscopy is a promising chemical sensor for in situ, on-site detection of contaminants. This technology has important advantages over other sensors: it can be used to identify hydrocarbons – capable of distinguishing between chemical groups such as alkanes and chlorinated, aromatic and polyaromatic hydrocarbons, as well as distinguishing compounds within the same homologous series of hydrocarbons. Furthermore, with the combined use of lipophilic polymer coatings and tip sensors, the waveguide can be turned into a localised chemical sensor. Coupled with the fact that the new generation of spectrometers are lower in cost and smaller in size than their predecessors, such a sensor can be installed in the field where communications technologies can transmit data from a remote location – ideally suited for alternative barriers as a means of monitoring the subsurface environment and the performance of the barrier.